Pengaruh Model Project-Based Learning (PjBL) dan Minat Belajar Terhadap Kemampuan Pemecahan Masalah Siswa - Haliliah, Haliliah; Arfini, Baiq Desy (Jurnal al Muta'aliyah: Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This research aims to determine the influence of the project-based learning (PjBL) model and interest in learning on the problem-solving abilities of MI Ma'arif Sirojul 'Ulum students. This type of research uses a quantitative approach, pre-experimental methods with a one-shot case study research design. The population in this study was class V, totaling 18 students. The instruments for this research are student perception questionnaires, learning inteest questionnaires and tests of students' problem-solving abilities. The data analysis technique uses multiple linear regression. The results of data analysis show that Fcount = 21.251 > Ftable = 3.26, meaning that there is an influence of the project-based learning (PjBL) learning model and interest in learning on students' problem-solving abilities. From the simultaneous t-test, it was found that tcount1 = 3.66 > ttable = 2.03 had a positive effect on students' problem-solving abilities. Meanwhile, for interest in learning, tcount 2 = 6.28 > ttable = 2.03 has a positive effect on students' problem-solving abilities. The magnitude of the influence of the project-based learning (PjBL) learning model and interest in learning on students' solving abilities is 56.3%.